HUBUNGAN TINGKAT STRES DENGAN KUALITAS TIDUR PADA MAHASISWA AKHIR S1 KESEHATAN MASYARAKAT UNIVERSITAS PAHLAWAN TUANKU TAMBUSAI TAHUN 2021 - Zurrahmi Z.R; Sri Hardianti; Fitria Meiriza Syahasti (PREPOTIF : JURNAL KESEHATAN MASYARAKAT, 2021)
Sleep is a basic need for everyone. In conditions of rest and sleep, the body performs a recovery process to restore the body's stamina to be in optimal condition. The impact of lack of sleep causes a person to have difficulty concentrating, fatigue, headaches, feeling unwell, lazy, decreased memory, confusion, and has an impact on the ability to make decisions. The purpose of this study was to analyze the relationship between stress levels and sleep quality in the final undergraduate students of Public Health at Pahlawan Tuanku Tambusai University in 2021. This type of research was a descriptive correlation study with a Cross Sectional design. This research was conducted in July 2021.2020 with a sample of 60 final undergraduate students in Public Health, Tuanku Tambusai University, obtained using a total sampling technique. Data collection techniques using a questionnaire. Analysis of the data used is univariate analysis and bivariate analysis with Chi Square test. The results showed that there was a significant relationship between stress levels and sleep quality in final students with p value = 0.003. By conducting this research, researchers expect students to prevent stress that can affect sleep quality.